Mitochondrial preconditioning: a potential neuroprotective strategy - Correia, Sónia C.; Carvalho, Cristina; Cardoso, Susana; Santos, Renato X.; Santos, Maria S.; Oliveira, Catarina; Perry, George; Zhu, Xiongwei; Smith, Mark A.; Moreira, Paula I. (Frontiers in Aging Neuroscience, 2010)
Mitochondria have long been known as the powerhouse of the cell. However, these organelles are also pivotal players in neuronal cell death. Mitochondrial dysfunction is a prominent feature of chronic brain disorders, including Alzheimer's disease (AD) and Parkinson's disease (PD), and cerebral ischemic stroke. Data derived from morphologic, biochemical, and molecular genetic studies indicate that mitochondria constitute a convergence point for neurodegeneration. Conversely, mitochondria have also been implicated in the neuroprotective signaling processes of preconditioning. Despite the precise molecular mechanisms underlying preconditioning-induced brain tolerance are still unclear, mitochondrial reactive oxygen species generation and mitochondrial ATP-sensitive potassium channels activation have been shown to be involved in the preconditioning phenomenon. This review intends to discuss how mitochondrial malfunction contributes to the onset and progression of cerebral ischemic stroke and AD and PD, two major neurodegenerative disorders. The role of mitochondrial mechanisms involved in the preconditioning-mediated neuroprotective events will be also discussed. Mitochondrial targeted preconditioning may represent a promising therapeutic weapon to fight neurodegeneration.